Expression of chicken interleukin-2 gene in Pichia methanolica - ZHOU Ji-yong; CHEN Ji-gang; WANG Jin-yong; ZHANG De-yong; ZHENG Xiao-juan (浙江大学学报. 农业与生命科学版, 2003)
Chicken interleukin-2 (chIL-2) is an important cytokine discovered recently. To explore a new approach to the expression of chIL-2 gene in methyltrophic yeast-Pichia methanolica (P. methanolica), the chIL-2 gene was obtained by PCR and inserted into the expression vector pMETαA. The recombinant P. methanolica PMAD11 strain (pMETαA/rchIL-2) was constructed using homologues recombination. SDS-PAGE and Western-blot analyses showed that the rchIL-2 protein was secreted successfully in the culture medium by P. methanolica PMAD11 strain, which have a molecular weight of 16 kDa, amounting to 35 percent of the total secreted proteins.